2005
DOI: 10.1369/jhc.4a6582.2005
|View full text |Cite
|
Sign up to set email alerts
|

Number and Distribution of Intraganglionic Laminar Endings in the Mouse Esophagus as Demonstrated with Two Different Immunohistochemical Markers

Abstract: S U M M A R YIntraganglionic laminar endings (IGLEs) represent the only vagal mechanosensory terminals in the tunica muscularis of the esophagus. Two specific markers for IGLEs were recently described in mouse: the purinergic P2 ϫ 2 receptor and the vesicular glutamate transporter 2 (VGLUT2). This study aimed at comparing both markers with respect to their suitability for quantitative analysis. We counted IGLEs immunostained for VGLUT2 and P2 ϫ 2 , respectively, and mapped their distribution in esophageal whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 34 publications
4
32
0
Order By: Relevance
“…In the esophagus, ATP released from esophageal keratinocytes may act in different ways on nerve endings that innervate the esophagus. ATP may reach and activate purinergic receptors expressed in intraganglionic laminar endings (23,37,45), since they are in intestine (3). Alternatively, vagal and spinal mucosal afferents may detect released ATP because they abut on and penetrate the esophageal epithelium with small branches (17,30,45).…”
Section: Resultsmentioning
confidence: 99%
“…In the esophagus, ATP released from esophageal keratinocytes may act in different ways on nerve endings that innervate the esophagus. ATP may reach and activate purinergic receptors expressed in intraganglionic laminar endings (23,37,45), since they are in intestine (3). Alternatively, vagal and spinal mucosal afferents may detect released ATP because they abut on and penetrate the esophageal epithelium with small branches (17,30,45).…”
Section: Resultsmentioning
confidence: 99%
“…L airway lumen pulmonary NEBs were applied (Brouns et al 2000(Brouns et al , 2002a(Brouns et al , b, 2003(Brouns et al , 2006aPintelon et al 2003). Because VGLUT1, VGLUT2 and P2X 2 receptor staining has been reported in putative vagal mechanosensory intraganglionic laminar endings (IGLEs) in the mouse esophagus (Castelucci et al 2003;Raab and Neuhuber 2005;Kraus et al 2007), this organ served as handy positive control in all of our en bloc lung-esophagus-heart cryostat sections. Moreover, for VGLUT1 and VGLUT2, the same antibodies as described in the latter studies were utilized (Raab and Neuhuber 2005;Kraus et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the en bloc dissection and sectioning of intrathoracic organs, the esophagus was typically included as a positive control for VGLUT1 (Kraus et al 2007), VGLUT2 (Raab and Neuhuber 2003) and P2X 2 receptor immunostaining (Castelucci et al 2003;Raab and Neuhuber 2005). Negative staining controls for all immunohistochemical procedures were performed by substitution of primary or secondary antisera for non-immune sera.…”
Section: Control Experiments For the Immunohistochemical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Myenteric mechanoreceptors showed none of characteristics of the leaf-like lamellar endings associated with IGLEs in the upper GI-tract, or rIGLEs in the lower GItract. Myenteric mechanoreceptors were readily identified by their immunoreactivity to the TRPV1 antibody and their immunoreactivity to the glutamate transporter, Vglut2, a reliable marker for extrinsic afferents in the GI-tract (Raab and Neuhuber, 2005;Zagorodnyuk and Brookes, 2003). These TRPV1 bulbous nodules were first identified morphologically in the distal colon of guinea pigs and mice in the immunohistochemical study by Ward et al (2003) but, at that stage, it was not shown that they behaved physiologically as a capsaicinsensitive low threshold mechanoreceptor.…”
mentioning
confidence: 99%